2010
DOI: 10.4293/108680810x12924466008006
|View full text |Cite
|
Sign up to set email alerts
|

Supracervical Robotic-Assisted Laparoscopic Sacrocolpopexy for Pelvic Organ Prolapse

Abstract: Supracervical robotic-assisted laparoscopic sacrocolpopexy was found to be an effective repair of apical vaginal defects in patients with pelvic organ prolapse who had not undergone previous hysterectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 27 publications
1
23
0
Order By: Relevance
“…Grade 1, 2, and 3 complications were 2 (<1%), 45 (3%), and 1 (<1%), respectively [12]. In particular, Satava grade 2 and 3 complications were 14 vaginotomies (1%), 26 bladder injuries (2%), 1 ureteral injury (<1%), and 4 bowel injuries (<1%) [10,11,16,17,[19][20][21][22][23]28,[31][32][33][34][35][36][38][39][40]. Additionally in one case (<1%), a suture with its needle was lost and a 2-cm incision for needle retrieval was necessary [25].…”
Section: Evidence Synthesismentioning
confidence: 96%
See 4 more Smart Citations
“…Grade 1, 2, and 3 complications were 2 (<1%), 45 (3%), and 1 (<1%), respectively [12]. In particular, Satava grade 2 and 3 complications were 14 vaginotomies (1%), 26 bladder injuries (2%), 1 ureteral injury (<1%), and 4 bowel injuries (<1%) [10,11,16,17,[19][20][21][22][23]28,[31][32][33][34][35][36][38][39][40]. Additionally in one case (<1%), a suture with its needle was lost and a 2-cm incision for needle retrieval was necessary [25].…”
Section: Evidence Synthesismentioning
confidence: 96%
“…Estimated blood losses were of limited entities; no studies reported a mean or median blood loss >150 ml [10,11,. Most studies reported a hospital stay <2 d [16,31,34,35]; three studies reported a median/mean hospitalization time >3 d [18,30,38]. However, the lack of uniformity in reporting operative parameters and the highly variable kinds of concomitant procedures performed (eg, the addition of concomitant hysterectomy) do not allow us to make a fair comparison between groups and evaluate how different surgical volume and different study periods influenced operative results.…”
Section: Evidence Synthesismentioning
confidence: 97%
See 3 more Smart Citations